KESESUAIAN FISIK DAN KIMIA PERAIRAN UNTUK BUDIDAYA Eucheuma cottoni DI GUGUS KEPULAUAN SALABANGKA KABUPATEN MOROWALI - Raihani Ya’la, Zakirah (FAPETKAN UNTAD, 2011)
This research was held in Morowali Regency from January to August 2010. Samples were taken at South Bungku in 5 villages: Waru – Waru, Jawi – Jawi, Kaleroang, Bunginkela and Buajangka. This study used survey method with taking sample directly in the study area by using simple random sampling, purposive sampling method and SIG method for land suitability. Image interpretation indicated that Eucheuma cottonii in station 1 in lack of harvest season, inappropriate class (S2) of 601,854 ha, inappropriate class (S3) of 2,363 ha, while in peak harvest season , appropriate class (S1) of 3,645 ha and less appropriate class of (S2) of 600,572 ha. Key words: Eucheuma cottonii, purposive sampling method and SIG